The impact of using the dynamic assessment developed by Dr. Reuven Feuerstein as an interactive approach to learn the english language . Aimed to students attending eighth basic year of Unidad Educativa “El Camino” during the period 2013-2014 - Martínez Noble, Karina del Rocío (2018)
The impact of applying the Dynamic Assessment thought a mediated learning experience developed by Dr. Reuven Feuerstein as an interactive approach to learn the English language for the students of Unidad Educativa El Camino. The study aimed to define Dr. Feuerstein’s approach to develop the learning potential of the students, establishing principles of application for the Dynamic Assessment thought a mediated learning experience and estimating learning potential on the basis of current performance through the application of a preliminary evaluation to analyze the dynamics of the learning process considering the interaction between teacher and the student. The approach consists on the application of a pre-test and a post-test to evaluate the learning conditions after the mediated learning experience, this methodology allows the teacher to strength and to improve the learning process taking into account the specific capabilities and skills of the students. The study show that the experimental application of the Dynamic Assessment improved the process of learning English, boosting the scores of the students. The mediated learning experience provided an individual interaction with the student. After the mediation, the instructor found that despite the fact that not all of the students developed a need of reflective thinking or disposition for conceptual thinking, the use of the methodology corrected and eliminated cognitive inefficiencies, improving the abilities of the students and developing intrinsic motivation. The Dynamic Assessment through a mediated learning experience was proposed for all the teachers of the Unidad Educativa El Camino in order to improve learning results.